Menikmati Secangkir Teh Nasgithel Rasa Yogyakarta - Rujiyanto, Rujiyanto (Humaniora, 2013)
Enjoying the art exhibition is like enjoying a cup of hot sweet tea in the afternoon. There are mixed feelings that we enjoy when walking by the spaces and searching for the meaning of artworks. Exhibition "Negari Ngayogyakarta" is a great exhibition of Yogyakarta, Sri Sultan Palace, and Hamengkubuwono IX. A very special exhibition is associated with the day of 100 years of the birth of a great leader of Ngayogyakarta Hadiningrat, Sultan HB IX. The exhibition was loaded with messages of journey of Yogyakarta and HB IX in the political role scene in the early period of independence until the present realities of Yogyakarta. Yogyakarta as the Kawah Candradimuka place to learn talented artists, reflected in the works of heavily loaded with the deepening of the concepts and ideas are very visionary and imaginary.